INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MULTIKULTURAL (Studi Multikasus di Sekolah Menengah Atas Negeri 1 Tanjunganom Nganjuk, Sekolah Menengah Atas Negeri 1 Nganjuk, dan Sekolah Menengah Kejuruan Negeri 1 Grogol Kediri) - Moh. Irmawan jauhari (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this research is to know the values of Multicultural Islamic Education and the internalization model of Multicultural Islamic Education values. With a qualitative approach and the type is multi-case. Researchers act as instruments as well as data collectors will conduct observations, interviews and document retrieval. Data analysis was carried out in two stages, namely: individual case data analysis and cross case analysis. The results of the study stated that the instilled Multicultural Islamic Education values aim to equip students with the ability to live in diversity. Islamic Education teachers become agents of internalization supported by school members and the community. The values of Islamic Religious Education have been integrated with Budi Pekerti which shows an emphasis on morals. The values offered so as not to be trapped in the formalities of learning, are strengthened by a local curriculum that aims to accommodate the need for a lack of multicultural attitudes based on multicultural values. The model of internalizing multicultural Islamic Education values in the learning process emphasizes exemplary, habituation and involvement of school members. Teachers in multicultural Islamic Education learning towards religious humanism.